Prevalence of frailty syndrome in old people in a hospital institution - Daniela Ramos Oliveira; Luiz Antonio Bettinelli; Adriano Pasqualotti; Débora Corso; Felipe Brock; Alacoque Lorenzini Erdmann (Universidade de São Paulo, 2013)
OBJECTIVE: to measure the prevalence of frailty syndrome in elderly inpatients in a hospital institution. METHODS: cross-sectional study using a sample of 99 subjects aged 65 or older, hospitalized in the month of November/2010 in São Vicente de Paulo Hospital in Passo Fundo, Rio Grande do Sul state (RS). Data were collected regarding the phenotype of the frailty, along with social and demographic, clinical and anthropometric information. RESULTS: the mean age was 74.5±6.8 years and 50 (50.5%) were women. 4% were classified as non-frail, 49 (49.5%) as pre-frail and 46 (46.5%) as frail. No statistically significant factors were identified that were associated with frailty. CONCLUSIONS: as was expected, the prevalence in this population was found to be high compared to other studies that focused on the community. It is believed that early detection and interdisciplinary intervention can prevent the progression of the condition and reduce the incidence of complications and hospitalization.